Peran Keluarga Dalam Proses Pembentukan Karakter di Mayarakat Pedesaan - Hani Mufidah; Ghufronudin; Yosafat Hermawan (Universitas Sarjanawiyata Tamansiswa, 2023)
Parents have a role in building children's character, especially in the village, but parents' problems are that it is difficult to apply basic character values to the environment where garbage is disposed of. This study aims to determine the process carried out in education to instill basic character values in individuals to build personality. This qualitative research was conducted using a case study approach in Dukuh Doplang, Sukosari Village. Research informants are mothers with two children. Data collection techniques in this study used observation, interviews, and documentation. The validity of the data uses source triangulation with data analysis through Pearson's theory. The findings in the field are that mothers have instilled the function of the family in the process of character formation regarding facts that occur in society which include adaptation, goal attainment, integration, and maintenance of patterns which become the process to achieve a character including cooperation, courtesy, responsibility and independently which will later become provisions from parents for children.